EVALUATION OF THE EFFECTIVENESS OF PREOPERATIVE PREPARATION AND POSTOPERATIVE MANAGEMENT OF PATIENTS WITH RETRO AND PROSPECTIVE PELVIC ORGAN PROLAPSE OF STAGE III - Nazarov B.B (Scholar Express Journals, 2023)
Genital prolapse remains one of the unsolved problems of modern gynecology
Keywords: Pelvic organ prolapse; genital prolapse; irrigation